1979
DOI: 10.1007/bf01961377
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of anion permeability by amphiphilic compounds in human red cell: Evidence for an interaction of niflumic acid with the band 3 protein

Abstract: In human erythrocyte, permeability to the anion is instantaneously, reversibly, and noncompetitively inhibited by the nonsteroidal anti-inflammatory drug, niflumic acid. The active form of this powerful inhibitor (I50 = 6 X 10(-7) M) is the ionic form. We demonstrated that: (i) The binding of niflumic acid to the membrane of unsealed ghosts show one saturable and one linear component over the concentration range studied. The saturable component vanishes when chloride transport is fully inhibited by covalently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 54 publications
3
29
0
Order By: Relevance
“…The ICo of niflumic acid against Ic(Ca) in Xenopus oocytes was estimated to be 17 #iM (White & Aylwin, 1990) which is almost an order less potent than against STICs at IC5o of about 2.5 x 10-1 M (Hughes & Segawa, 1993). Also niflumic acid is a potent inhibitor (ICm of 6.3 x 10-7 M) of anion exchange in human red cells where it has been suggested that niflumic acid interacts with the band 3 protein (Cousin & Motais, 1979). It is interesting that many compounds that block chloride channels also inhibit anion transport in red blood cells (also see Cousin & Motais, 1982a,b).…”
Section: Discussionmentioning
confidence: 99%
“…The ICo of niflumic acid against Ic(Ca) in Xenopus oocytes was estimated to be 17 #iM (White & Aylwin, 1990) which is almost an order less potent than against STICs at IC5o of about 2.5 x 10-1 M (Hughes & Segawa, 1993). Also niflumic acid is a potent inhibitor (ICm of 6.3 x 10-7 M) of anion exchange in human red cells where it has been suggested that niflumic acid interacts with the band 3 protein (Cousin & Motais, 1979). It is interesting that many compounds that block chloride channels also inhibit anion transport in red blood cells (also see Cousin & Motais, 1982a,b).…”
Section: Discussionmentioning
confidence: 99%
“…This effect on chloride efflux has been described in sympathetic neurones where it was found that reduced extracellular chloride depleted intracellular chloride over time, or after repeated applications of GABA (Adams & Brown, 1975 Senktide and GABAA currents were blocked by the fenamates, niflumic and mefenamic acid. These drugs block anion transport (Cousin & Motais, 1979) and anion channels (White & Aylwin, 1990). Fenamates can also block cation conductances (Gogelein, Dahlem, Englert & Lang, 1990), but not cation transport (Cousin & Motais, 1979).…”
Section: Characterization Of Neuronesmentioning
confidence: 99%
“…These drugs block anion transport (Cousin & Motais, 1979) and anion channels (White & Aylwin, 1990). Fenamates can also block cation conductances (Gogelein, Dahlem, Englert & Lang, 1990), but not cation transport (Cousin & Motais, 1979). It is unlikely that the fenamates were blocking cation channels in the present study as fEPSPs in S-neurones were unaffected by these drugs.…”
Section: Characterization Of Neuronesmentioning
confidence: 99%
“…Other inhibitors of some anion-transport systems were tested extracellularly: furosemide (up to 1 mM; see Burg, Stoner, Cardinal & Green, 1973), penicillin 297 D. CHESNO Y-MARCHAIS (sodium benzylpenicillinate, up to 10 mM; see Hochner, Spira & Werman, 1976) and niflumic acid (up to 20/SM; see Cousin & Motais, 1979) had no effect on the Cl-current. Higher doses of niflumic acid seemed toxic, inducing a large increase in membrane conductance.…”
Section: Effects Of Depolarizing Pre-pul8ebmentioning
confidence: 99%